THE INFLUENCE OF NANOSECOND ELECTROMAGNETIC PULSES TO OBTAIN TIN AND THE PROPERTIES OF ITS ALLOYS - V. G. Komkov; V. V. Gostishchev; Hosen Ri; E. H. Ri; S. V. Dorofeev; G. A. Knyazev (Литьë и металлургия)
Experimentally found that the effect of nanosecond electromagnetic pulses to melt the charge, while the carbon thermal recovery of the tin ore, accelerates the formation of the metallic phase.